Living on the edge: Assessing the diversity of South African Pocillopora on the margins of the Southwestern Indian Ocean - (:unkn) unknown (My University, 2019)
Scleractinia of the Maputaland reef complex (MRC) in South Africa exist at the margins of the Western Indian Ocean (WIO) coral distribution and are the only substantial hermatypic coral communities in South Africa. Pocillopora species occupy a conspicuous component of the MRC, and previous investigations identified three species of Pocillopora utilizing conventional taxonomy. Thus, our aims were four-fold: to elucidate Pocillopora species diversity using genetic techniques, primarily using species delimitation methods based on the ORF gene; to test for the presence of hybridisation within the Pocillopora community on the SouthWest margin of distribution in the Indian Ocean using two nuclear and two mitochondrial markers; to test the presence of cryptic species, using 13 microsatellite markers, finally, to elucidate the degree of genetic diversity within each Pocillopora species found and compare this to communities in lower latitudes. We illustrate taxonomic inconsistencies between these inventories and our phylogenetic data. The MRC harbours unique populations of Pocillopora, consisting of three species hypothetically co-occurring throughout the south WIO, namely: P. meandrina/P. eydouxi, commonly misidentified as P. verrucosa, P. verrucosa, sometimes correctly identified, but also commonly misidentified as P. damicornis sensu lato, and P. villosa, almost always misidentified as P. eydouxi. The hypothesis that hybrid swarms of Pocillopora occur in marginal environments such as the MRC was not supported, with low levels of introgressive hybridization reported instead. Analyses illustrate low genetic diversity at the species and population resolutions, suggesting a small founder population for each species. Nevertheless, these populations are demographically unique, exhibiting high levels of ITS2 haplotype endemism compared to higher latitude populations and the rest of the WIO. Pocillopora diversity on the MRC represents a unique assemblage and warrant
Keywords: African Research